Feuchtwanger and Judaism - Wallace, Ian,Lerner, Paul,Stern, Frank (Peter Lang Ltd, 2019)
This collection of essays is devoted to the Jewish themes that ran through Lion Feuchtwanger’s life, works and worlds. Beginning with a selection of Feuchtwanger’s unpublished writings, speeches, and interviews, the volume examines the author’s approaches to Jewish history, Zionism, Judaism’s relationship to early Christianity and to eastern religions, and Jewish identity through his works, above all his historical fiction. Essays also trace translations of his works into English and Russian, and the meaning of his writing for various communities of Jewish and non-Jewish readers in Britain, North America, and the Soviet Union. A final section frames the issues around Feuchtwanger and Jewishness more broadly by considering the condition of exile and expanding the focus to communities of émigré writers and political figures in North America and beyond.
10.3726/b14359